Prostaglandin F2α and EP2 agonists, and a ROCK inhibitor modulate the formation of 3D organoids of Grave's orbitopathy related human orbital fibroblasts. (April 2021) - Ichioka, Hanae; Ida, Yosuke; Watanabe, Megumi; Ohguro, Hiroshi; Hikage, Fumihito
Abstract: 3D organoid cultures were used to elucidate the periocular effects of several anti-glaucoma drugs including a prostaglandin F2α analogue (bimatoprost acid; BIM-A), EP2 agonist (omidenepag; OMD) or a Rho-associated coiled-coil containing protein kinase (ROCK) inhibitor (ripasudil; Rip) on Grave's orbitopathy (GO) related orbital fatty tissue. 3D organoids were prepared from GO related human orbital fibroblasts (GHOFs) obtained from patients with GO. The effects of either 100 nM BIM-A, 100 nM OMD or 10 μM Rip on the 3D GHOFs organoids were examined with respect to organoid size, physical properties by a micro-squeezer, and the mRNA expression of extracellular matrix (ECM) proteins including collagen (COL) 1, COL 4, COL 6, and fibronectin ( FN ), ECM regulatory genes including lysyl oxidase ( LOX ), Connective Tissue Growth Factor ( CTGF ) and inflammatory cytokines including interleukin-1β (IL1β ) and interleukin-6 ( IL6 ). The size of the 3D GHOFs organoids decreased substantially in the presence of BIM-A, but also increased substantially in the presence of the others (OMD or Rip). The physical stiffness of the 3D GHOFs organoids was significantly decreased by Rip. BIM-A caused significantly the down-regulation of three ECM genes, Col 1, Col 6 and Fn, and two ECM regulatory genes and the up-regulation of IL6 . In the presence of OMD, two ECM genes, Col 1 and Fn, and LOX were significantly down-regulated but IL1β and IL6 were significantly up-regulated. In the case of Rip, Col 1, FN and CTGF were significant down-regulated. Our present findings indicate that anti-glaucoma drugs modulate the structures and physical properties 3D GHOFs organoids in different manners by modifying the gene expressions of ECM, ECM regulatory factors and inflammatory cytokines. The results indicate that the benefits and demerits of anti-glaucoma medications need to be scrutinized carefully, in cases of patients with GO. Highlights: Antiglaucoma drugs markedly affect orbital fatty tissues from Grave's orbitopathy. Bimatoprost decreases the volume of orbital fibroblasts of Grave's orbitopathy. Ripasudil increases the volume of orbital fibroblast of Grave's orbitopathy. Three-dimension cultures are useful for studying drug-induced periocular effects.